The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d1ta10545k
|View full text |Cite
|
Sign up to set email alerts
|

From vanadium slag to multi-cation-intercalated V2O5·nH2O: low-cost direct synthesis and high-performance aqueous battery application

Abstract: Although hydrated vanadate compounds have received extensive attention in aqueous batteries for their high specific capacity, they are still impeded by the poor cycling resulting from host structure degradation and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…In regard to cathode materials, vanadium-based oxides have been widely investigated due to their suitable open framework, controllable morphology, rich valence states, and stable cycle stability. , As such, the electrochemical performances of a variety of vanadium-based oxides such as layered vanadates, V 3 O 7 , , V 6 O 13 , and VO 2 have been studied in RAZIBs. For instance, multi-cation intercalated hydrated vanadate prepared from vanadium slag demonstrates ultrahigh rate performance in RAZIBs . Recently, spinel oxides gain increasing attention due to their crystal stability, tunable atomic-scale structure, and suitable working voltage. , For instance, ZnMn 2 O 4 spinel oxide with structural defects exhibits facilitated ion diffusion kinetics, leading to promising Zn 2+ storage capability and stable cycle stability. , The presence of rich lattice water in ZnMn 2 O 4 demonstrates a reduced intercalation energy barrier, resulting in high-power performance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to cathode materials, vanadium-based oxides have been widely investigated due to their suitable open framework, controllable morphology, rich valence states, and stable cycle stability. , As such, the electrochemical performances of a variety of vanadium-based oxides such as layered vanadates, V 3 O 7 , , V 6 O 13 , and VO 2 have been studied in RAZIBs. For instance, multi-cation intercalated hydrated vanadate prepared from vanadium slag demonstrates ultrahigh rate performance in RAZIBs . Recently, spinel oxides gain increasing attention due to their crystal stability, tunable atomic-scale structure, and suitable working voltage. , For instance, ZnMn 2 O 4 spinel oxide with structural defects exhibits facilitated ion diffusion kinetics, leading to promising Zn 2+ storage capability and stable cycle stability. , The presence of rich lattice water in ZnMn 2 O 4 demonstrates a reduced intercalation energy barrier, resulting in high-power performance .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, multi-cation intercalated hydrated vanadate prepared from vanadium slag demonstrates ultrahigh rate performance in RAZIBs. 24 Recently, spinel oxides gain increasing attention due to their crystal stability, tunable atomic-scale structure, and suitable working voltage. 25,26 For instance, ZnMn 2 O 4 spinel oxide with structural defects exhibits facilitated ion diffusion kinetics, leading to promising Zn 2+ storage capability and stable cycle stability.…”
Section: Introductionmentioning
confidence: 99%
“…By equivalent-circuit fitting, the R ct value was determined as 79 and 148 Ω for YMO-0.1 and MO, respectively. The smaller R ct value indicates better electrical conductivity of the cathode, 52,53 which is attributed to the narrower band gap of the YMO-0.1 sample (Fig. 2i).…”
Section: Nanoscale Papermentioning
confidence: 98%
“…[68] Recently, Chen et al synthesized a multi-ion pre-co-intercalated hydrate vanadate (M x V 2 O 5 •nH 2 O) directly from vanadium slag waste, and the vanadate showed inspiring performance as the cathode material for zinc-ion batteries. [69] It has also been revealed that the cations in vanadium slag, such as Fe, Mg, and Ti, are beneficial in stabilizing the interlayer structure and improving the reaction kinetics.…”
Section: Chemsuschemmentioning
confidence: 99%